Implementation of the Merdeka Curriculum in Vocational High School Accounting and Financial Institutions Program - Sefialdila Kharis Fatima; Sari Dhany Efita (LPPM STKIP Kusuma Negara, 2026)
The purpose of this study was to determine the implementation of the Merdeka Curriculum at SMK N 1 Sragen, particularly in the Accounting and Institutional Finance Program, to identify the planning and implementation of Merdeka Curriculum-based learning, and to describe the implementation of the Pancasila Student Profile Strengthening Project (P5). The data collection techniques used were interviews, observation, and documentation. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The results of the study showed that the implementation of the Merdeka Curriculum in vocational high schools in the Accounting and Institutional Finance Program has generally been carried out in accordance with the concepts and stages of the Merdeka Curriculum. Teachers and students feel that they are given the flexibility to develop learning materials in accordance with the characteristics and needs of the students. In addition, the Merdeka Curriculum also provides opportunities for students to develop independent learning and hone their skills, including public speaking, learning to express opinions, and increasing creativity and broadening their knowledge. Through P5 activities, students receive more meaningful, relevant, and student-centered education with an emphasis on character building in accordance with the Pancasila Student Profile.